Synthesis and characterization of Na+, K+, Ca2+, Ba2+, Sr2+, and Pb2+ complexes with some lipophilic diaza-18-crown-6 derivatives - Temel, H; Hosgören, H; Boybay, M (Marcel Dekker Inc, 2002)
In this study, the complexes of 7,16-Dibenzyl-4,7,10,13-tetraoxa-7,16-diazacyclooctadecane; 7,16-Dihexzyl-4,7,10,13tetraoxa-7,16-diazacyclooctadecane; 7,16-Diheptyl-4,7,10,13tetraoxa-7,16-diazacyclooctadecane; 7,16-Dioctyl-4,7,10,13tetraoxa-7,16-diazacyclooctadecane; 7,16-Dinonyl-4,7,10,13tetraoxa-7,16-diazacyclooctadecane; 7,16-Didodecyl 4,7,10, 13-tetraoxa-7,16-diazacyclooctadecane with Na+, K+, Ca2+, Ba2+, Sr2+ and Pb2+ were prepared by using perchlorates salts. Their complexes were produced by adding the solution of metal salts in ethyl alcohol to the solution of ligand in ethyl alcohol. The complexes obtained were filtered and washed with ethyl alcohol and recrystallizied in ethyl alcohol and dried in vacuum. Their complexes were investigated by using Elemental Analysis, and infrared (IR). Observed H-1 NMR,C-13 NMR, and C-13 chemical shifts are discussed in terms of conformational changes of the macrocycle.
Keywords: IR; H-1/C-13 NMR diazamacrocycles; metal complexes